THE SIGNIFICANCE OF THE COGNITIVE APPROACH IN ENHANCING STUDENTS PHRASEOLOGICAL COMPETENCE - Kushiyeva Nodira Xabibjonovna; Roziboyev Kuvonchbek Ergash og'li (Web of Journals Publishing, 2025)
Phraseological competence, as a crucial component of language proficiency, plays a fundamental role in mastering a foreign language. It encompasses the ability to understand, interpret, and appropriately use idiomatic expressions, collocations, and fixed phrases, which are deeply embedded in the cultural and cognitive framework of native speakers.
Keywords: Cognitive approach, phraseological competence, translation, knowledge, phraseological units.